Controlling of tunneling resistance in carbon nanofiber polymer composites: A novel equation for polymer tunneling resistivity by quantifiable parameters - Yasser Zare; Muhammad Naqvi; Kyong Yop Rhee; Soo-Jin Park (Journal of Materials Research and Technology)
High polymer tunneling resistivity (ρ) enhances tunneling resistance, thereby restricting electron transferring in nanocomposites; however, ρ remains an ambiguous parameter. In this work, two developed models for electrical conductivity of carbon nanofiber (CNF) polymer samples (PCNFs) are integrated to express ρ by CNF characteristics (concentration, conductivity, percolation threshold, size and waviness), interphase depth, network fraction, and tunneling dimensions (length and diameter). Extensive experimental data are used to validate the models. Furthermore, ρ is calculated for several samples from prior studies. The effects of various factors on ρ are analyzed to confirm the validity of the proposed equation. The resulting patterns elucidate the key parameters governing ρ in PCNFs. A lower percolation threshold, thicker interphase, higher network fraction, greater CNF conductivity, along with shorter and wider tunnels, lead to reduced ρ. The maximum ρ, recorded at 1600 Ω m, occurs at a CNF radius (R) = 100 nm and CNF length (l) = 40 μm, while R < 70 nm or l > 80 μm decreases ρ to 87 Ω m. Thus, thinner or longer nanofibers substantially reduce the ρ improving the charge transferring.